Perceiving locations of moving objects across eyeblinks - Gerrit, Maus (2022)
Eyeblinks cause disruption of visual input that generally goes unnoticed. It is thought that the brain uses active suppression to prevent awareness of the gaps, but it is unclear how suppression would affect the perception of dynamic events when visual input changes across the blink. Here, we addressed this question by studying the perception of moving objects around eyeblinks. In Experiment 1 (N = 16), we observed that when motion terminates during a blink, the last perceived position is shifted forward from its actual last position. In Experiment 2 (N = 8), we found that motion trajectories were perceived as more continuous when the object jumped backward during the blink, canceling a fraction of the space that it traveled. This suggests subjective underestimation of blink duration. These results reveal the strategies used by the visual system to compensate for disruptions and maintain perceptual continuity: Time elapsed during eyeblinks is perceptually compressed and filled with extrapolated information.